Students Satisfaction on Scaffolding Strategy by Teacher in Teaching Reading Comprehension - Novita, Devi; Arifmiboy, Arifmiboy (Journal of Educational Management and Strategy, 2023)
The research was due to several problems found in the field; the students find it difficult in the learning process so that they have difficulty understanding the main idea and students are noisy on learning process. The students not interseted on learning process because they lake of motivation, more stdeunts be passive in the class. Besides, the research is aimed to find out students satisfaction on scaffolding strategy use by teacher in teacing reading comprehension at the tenth grade at SMK Pembangunan Bukitinggi 2021/2022. The research used descriptive quantitative research by using questionnaire as an instrument. The researcher used purposive sampling technique. The sample of this research was X TM, X TO 1, X TO 2, X TKI at SMK 4 Pembangunan that were 68 students as sample. The data was collected by distributing questionnaires. In addition, analyzing data was done by identifying researcher respond, analyzing data and making conclusion related to quality rating level. The result of the research were; first, students’ satisfaction on the use use scaffolding strategy by teacher in teaching rading comprehension in pre reading stage was 60,98%% means high level. Second, students’ satisfaction on scaffolding strategy in reading stage was 59,52% means high enough level. Third, students’ satisfaction on use scaffolding strategy in post reading stage it was 62,35% means high level. It can be concluded that students tend to have satisfaction in interpeted high level in reading comprehension use scaffolding strategy at tenth grade SMK Pembangnan Bukitinggi was used in the classroom. Abstrak Penelitian ini disebabkan oleh beberapa permasalahan yang ditemukan di lapangan; siswa merasa kesulitan dalam proses pembelajaran sehingga kesulitan memahami gagasan pokok dan siswa ribut dalam proses pembelajaran. Siswa kurang tertarik dalam proses pembelajaran karena kurangnya motivasi, siswa lebih banyak yang pasif di kelas. Selain itu, penelitian ini bertujuan untuk mengetahui kepuasan siswa terhadap strategi scaffolding yang digunakan oleh guru dalam mengajar pemahaman membaca di kelas sepuluh di SMK Pembangunan Bukitinggi 2021/2022. Penelitian ini menggunakan penelitian deskriptif kuantitatif dengan menggunakan kuesioner sebagai instrumennya. Peneliti menggunakan teknik purposive sampling. Sampel penelitian ini adalah X TM, X TO 1, X TO 2, X TKI di SMK 4 Pembangunan yang berjumlah 68 siswa sebagai sampel. Pengumpulan data dilakukan dengan menyebarkan kuesioner. Selain itu, analisis data dilakukan dengan mengidentifikasi respon peneliti, menganalisis data dan membuat kesimpulan terkait tingkat penilaian kualitas. Hasil penelitian tersebut adalah; pertama, kepuasan siswa terhadap penggunaan strategi scaffolding oleh guru dalam mengajarkan pemahaman nilai pada tahap pra-membaca adalah 60,98%% berarti tingkat tinggi. Kedua, kepuasan siswa terhadap strategi scaffolding pada tahap membaca sebesar 59,52% berarti tingkat cukup tinggi. Ketiga, kepuasan siswa terhadap penggunaan strategi scaffolding pada tahap pasca membaca sebesar 62,35% berarti tinggi. Dapat disimpulkan bahwa siswa cenderung mempunyai kepuasan dalam interpetasi tingkat tinggi dalam pemahaman membaca menggunakan strategi scaffolding di kelas sepuluh SMK Pembangnan Bukitinggi yang digunakan di dalam kelas.